The Model of Entrepreneurial Commitment: Strategies for Improving Student Start-Up Business Performance - Nuryana, Ita; Margunani, Margunani (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
The classic factor determining the performance of a micro business from the financial side is the working capital management but some of these efforts often fail because of entrepreneurial commitment issues. The existence of such phenomena has pushed further to reveal the role of entrepreneurial commitment in increasing the role of working capital management on business performance. This study aimed to determine the effect of working capital management on student start-up performance that is moderated by entrepreneurial commitment. This research was a quantitative research. The sample in this study was 169 student start-up businesses throughout the Province of Central Java. Analysis of the data in this study used moderate regression analysis (MRA). Through the Moderating Regression Analysis (MRA) the results of this study indicated that entrepreneurial commitment moderated the effect of working capital management on the sustainability of start-up, while working capital had no effect on business performance. The implication of this research was the development of risk and return theory by making entrepreneurial commitment as a reinforcement of the effect of working capital management on business performance.